2016
DOI: 10.1159/000446906
|View full text |Cite
|
Sign up to set email alerts
|

Factors That Modulate Neurogenesis: A Top-Down Approach

Abstract: Although hippocampal neurogenesis in the adult brain has been conserved across the vertebrate lineage, laboratory studies have primarily examined this phenomenon in rodent models. This approach has been successful in elucidating important factors and mechanisms that can modulate rates of hippocampal neurogenesis, including hormones, environmental complexity, learning and memory, motor stimulation, and stress. However, recent studies have found that neurobiological research on neurogenesis in rodents may not ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…Decreased environmental complexity within the laboratory creates lower demands on learning and memory, which is correlated with decreased brain attributes, particularly in the mammalian hippocampus and hippocampal homologues in other vertebrates [90]. The effects of environmental complexity are even more apparent when comparing laboratory-reared and field-caught conspecifics; previous studies in mammals, birds, reptiles and fish found that individuals either hatched/born or housed long-term in the laboratory have smaller hippocampi/cortices and decreased neurogenesis than their field-caught counterparts [91][92][93][94][95][96][97][98][99]. Thus, while CORT and FA treatments were sufficient to decrease cortical volume in the lab, the ability to detect the effects of intergenerational stress on the brain, if they exist, may have been diminished due to cortical development in a simplistic laboratory environment.…”
Section: (B) the Effects Of Intergenerational Stress On The Neural Ph...mentioning
confidence: 99%
“…Decreased environmental complexity within the laboratory creates lower demands on learning and memory, which is correlated with decreased brain attributes, particularly in the mammalian hippocampus and hippocampal homologues in other vertebrates [90]. The effects of environmental complexity are even more apparent when comparing laboratory-reared and field-caught conspecifics; previous studies in mammals, birds, reptiles and fish found that individuals either hatched/born or housed long-term in the laboratory have smaller hippocampi/cortices and decreased neurogenesis than their field-caught counterparts [91][92][93][94][95][96][97][98][99]. Thus, while CORT and FA treatments were sufficient to decrease cortical volume in the lab, the ability to detect the effects of intergenerational stress on the brain, if they exist, may have been diminished due to cortical development in a simplistic laboratory environment.…”
Section: (B) the Effects Of Intergenerational Stress On The Neural Ph...mentioning
confidence: 99%
“…In birds, adult neurogenesis takes place in numerous brain regions throughout life, including the hippocampus. The role of the avian hippocampus in (especially spatial) learning and memory is well established (Roth et al, 2010) and new-born neurons are suspected to play an important role in this process (LaDage, 2016). A potential role of the hippocampus and its new-born neurons in emotional regulation is only starting to emerge (Smulders, 2017).…”
Section: The Hippocampus As a Biomarker Of Cumulative Affective Expermentioning
confidence: 99%
“…While many of the aforementioned studies have leveraged naturally occurring hormonal changes across seasons, between the sexes, or across species to examine these relationships, there are genetic, population-level, and other life history variables that can introduce variance not attributable to differences in neuroendocrinology (e.g., Knapp, 2003 ; Moore, 1991 ; LaDage, 2016 ). One way to circumvent some of these issues is to utilize model species that demonstrate polymorphisms within a sex.…”
Section: Introductionmentioning
confidence: 99%